Analisa Karakteristik Marshall Pada Campuran Asphalt Concrete-Binder Course ( AC-BC ) Menggunakan Limbah Beton Sebagai Coarse Aagregat - Muhammad, Isyak Bayu; , Ir. Agus Riyanto, M.T; , Senja Rum Harnaeni, S.T, M.T (2016)
Making the pavement requires a lot of aggregates , while the aggregate is a natural resource that is not renewable in addition as the rapid development in Indonesia will require many new aggregate . Buildings are unfit for use or have entered the age of the plan it will be destroyed and produce concrete waste that much anyway , see the phenomenon it is necessary to return the waste concrete used during wasted and not very useful . This study was conducted to know Marshall characteristics when used as a partial replacement of coarse aggregate in a mixed type AC - BC ( Asphalt - Concrete Binder Course ). . This study begins by examining the characteristics of the new aggregate and concrete waste which is then followed to determine the optimum bitumen content variation asphalt content of 4.5% , 5 % , 5.5 % , 6 % , 6.5 % and 7 % of the total mixture . For the combined mixture gradation and values Mashall properties refer to the specifications of Highways 2010 Division 6 ( revision 3 ) . Having obtained the optimum bitumen content we then make a specimen with concrete waste concrete levels of 0 % , 20 % , 40 % , 60 % , 80 % of the total coarse aggregate . Marshall then test and obtained values characteristic Marshall Based on the research results , the use of waste concrete as a partial replacement of coarse aggregate meets the specifications required by the Highways 2010 as a replacement for coarse aggregate in the mix AC - BC ( Asphalt - Concrete Binder Course ) . Partial replacement of coarse aggregate using waste effect on the characteristics of concrete Marshall and obtained optimum levels of 8 % of the total coarse aggregate and the results of research in the can VIM , VMA and Flow increased , whereas stability , Marshall Quetient and VFWA decreased . The VIM value was obtained at a level of 80 % of waste concrete that is 15.8 % , the biggest VMA at a level of 80% of waste concrete that is 26.99 % , the largest flow at a level concrete waste 80 % of 4.5 mm , for the stability of the largest value in without waste concrete mix is 1638.07 kg , for Marshall Quetient largest value in the mix without waste concrete is 512.13 kg / mm , while the value of the largest VFWA also be in the mix without waste concrete that is 77.96 % .